Serum Lactate Dehydrogenase Level as a Prognostic Factor for COVID-19: A Retrospective Study Based on a Large Sample Size - Huang, Yihui; Guo, Liang; Chen, Jiwei; Wu, Meng; Zhang, Chao; Liu, Zeming; Li, Jinpeng; Li, Kun; Xiong, Zhongwei; Wu, Qian; Li, Zhengwei; Luo, Kuan; et al. (Frontiers in Medicine, 2022)
Background: In this study, we investigated the relationship between serum lactate dehydrogenase (LDH) level and disease progression and prognosis of patients with COVID-19. Methods: We retrospectively reviewed the information of 1751 patients with COVID-19 from Leishenshan Hospital in Wuhan, China. Univariate and multivariate Cox regression analyses as well as Logistics regression analyses, and Kaplan-Meier curves were used to determine the association between LDH levels and the prognosis of COVID-19 patients. Results: LDH was an independent risk factor for in-hospital death no matter it was taken as classified variable and continuous variable (all P=0.001) but not for severe or critical illness status. The Kaplan-Meier curves for LDH level showed that an elevated level of LDH was associated with in-hospital death. Conclusions: In patients with COVID-19, the increased LDH level is associated with a higher risk of negative clinical prognosis and higher mortality. This will provide a reference for clinicians and researchers to understand, diagnose, and treat patients with COVID-19. Further prospective studies with larger sample sizes are needed to verify these findings.